The Role of Extracellular Histones in Influenza Virus Pathogenesis - Ashar, Harshini K; Mueller, Nathan C; Rudd, Jennifer M; Snider, Timothy A; Achanta, Mallika; Prasanthi, Maram; Pulavendran, Sivasami; Thomas, Paul G; Ramachandran, Akhilesh; Malayer, Jerry R; Ritchey, Jerry W; Rajasekhar, Rachakatla; et al. (The American journal of pathology, 2018)
Although exaggerated host immune responses have been implicated in influenza-induced lung pathogenesis, the etiologic factors that contribute to these events are not completely understood. We previously demonstrated that neutrophil extracellular traps exacerbate pulmonary injury during influenza pneumonia. Histones are the major protein components of neutrophil extracellular traps and are known to have cytotoxic effects. Here, we examined the role of extracellular histones in lung pathogenesis during influenza. Mice infected with influenza virus displayed high accumulation of extracellular histones, with widespread pulmonary microvascular thrombosis. Occluded pulmonary blood vessels with vascular thrombi often exhibited endothelial necrosis surrounded by hemorrhagic effusions and pulmonary edema. Histones released during influenza induced cytotoxicity and showed strong binding to platelets within thrombi in infected mouse lungs. Nasal wash samples from influenza-infected patients also showed increased accumulation of extracellular histones, suggesting a possible clinical relevance of elevated histones in pulmonary injury. Although histones inhibited influenza growth in vitro, in vivo treatment with histones did not yield antiviral effects and instead exacerbated lung pathology. Blocking with antihistone antibodies caused a marked decrease in lung pathology in lethal influenza-challenged mice and improved protection when administered in combination with the antiviral agent oseltamivir. These findings support the pathogenic effects of extracellular histones in that pulmonary injury during influenza was exacerbated. Targeting histones provides a novel therapeutic approach to influenza pneumonia.